2022
DOI: 10.3390/ijerph192114299
|View full text |Cite
|
Sign up to set email alerts
|

Operationalization and Reporting Practices in Manuscripts Addressing Gender Differences in Biomedical Research: A Cross-Sectional Bibliographical Study

Abstract: Historically, authors in the biomedical field have often conflated the terms sex and gender in their research significantly limiting the reproducibility of the reported results. In the present study, we investigated current reporting practices around gender in biomedical publications that claim the identification of “gender differences”. Our systematic research identified 1117 articles for the year 2019. After random selection of 400 publications and application of inclusion criteria, 302 articles were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Sex and gender are two separate terms that both impact on health; however, they tend to be conflated in medicine. A 2022 study of biomedical publications found that the term 'gender differences' only analyzed and reported biological occurrences, demonstrating how such terminology is still used interchangeably and incorrectly in medical research [56]. Sex refers to characteristics that are biological and physiological that define men and women, whereas gender describes socially constructed characteristics, norms, and behaviors that supposedly characterize women and men [57].…”
Section: Gender Differences In Health Gender and Clinical Trialsmentioning
confidence: 99%
“…Sex and gender are two separate terms that both impact on health; however, they tend to be conflated in medicine. A 2022 study of biomedical publications found that the term 'gender differences' only analyzed and reported biological occurrences, demonstrating how such terminology is still used interchangeably and incorrectly in medical research [56]. Sex refers to characteristics that are biological and physiological that define men and women, whereas gender describes socially constructed characteristics, norms, and behaviors that supposedly characterize women and men [57].…”
Section: Gender Differences In Health Gender and Clinical Trialsmentioning
confidence: 99%
“…Recent research shows that 29% of the scientific biomedical articles claiming to assess gender differences actually focus on sex differences. 18 This blurring of the concepts mixes up the relative contribution of sex and gender to health outcomes, ultimately affecting the validity of conclusions drawn from research and thereby the efficacy of policymaking and health interventions. Although sex and gender are continuously shaping each other, the two concepts are different and we do not necessarily consider one as the direct consequence of the other.…”
Section: Sex Gender and Healthmentioning
confidence: 99%
“…Studies of the physical or physiological aspects of work may benefit from the consideration of sex (biological differences). In contrast, studies of the social, identity, or power aspects of work may benefit from consideration of gender (social roles) [17]. Because of the interconnected nature of the physical and social dimensions of exposure, it can be challenging to draw clear distinctions between sex and gender in practice [18].…”
Section: Introductionmentioning
confidence: 99%